Interactions between two neotropical phytoseiid predators and consequences for biological control of a shared prey - Onzo, A.; Hanna, R.; Janssen, A.; Sabelis, M. (Informa UK Limited, 2004)
The issue of introducing single or multiple natural enemy species for classical biological control has been an area of intense inquiry by ecologists and biological control practitioners. This is particularly relevant to classical biological control of cassava green mite Mononychellus tanajoa (Bondar) (Tetranychidae) in Africa, as this pest mite is shared by several natural enemies in the Neotropics (its area of origin), two of which have been introduced and established widely in Africa. We conducted two screenhouse experiments using the two neotropical phytoseiid predatory mites, Typhlodromalus aripo DeLeon and Typhlodromalus manihoti Moraes, to determine the effects of single and two-predator species on population dynamics of the two predators and on suppression of M. tanajoa populations. The two predators are thought to be complementary in their impact on their shared prey M. tanajoa, due to similarities in their preference for this prey and to differences in their spatial distribution and foraging activities on cassava. The two predator species were released alone or together at low and at high initial densities of M. tanajoa. In all cases, predator releases resulted in significant suppression of M. tanajoa, but the degree of suppression did not differ among single and two-species releases with one exception: at high initial density of M. tanajoa, releases of T. aripo alone had less impact than that of either T. manihoti alone or of the two species together. Typhlodromalus aripo also appeared to be inferior as a competitor of T. manihoti: at low initial density of M. tanajoa, the proportion of T. aripo in the two-predator release treatments gradually declined and was strikingly lower than in the single species release, probably due to intraguild predation on its larvae by T. manihoti. However, T. aripo persisted longer than T. manihoti after elimination of M. tanajoa. On the basis of this study under semi-natural conditions, it appears that either species is sufficient for controlling M. tanajoa populations, with T. manihoti being more efficient at high initial prey densities and T. aripo at low initial prey densities. At high prey density, T. manihoti increased to large numbers and outcompeted T. aripo. Relevance of these findings to larger spatial scale and under natural conditions is discussed.